Local Wisdom Values in the ‘Takneul’ Oral Tradition of the Bunak Tribe of East Nusa Tenggara: A Metaphorical Ecolinguistic Study - Fransiskus Yoga Oktavian Bele Bau; R. Kunjana Rahardi (JURNAL ARBITRER, 2023)
This study aims to describe the values of local wisdom in the Takneul oral tradition of the Bunak people, East Nusa Tenggara from a metaphorical ecolinguistic perspective. This research is a qualitative research with a simplified Spradley ethnographic approach for collecting data researchers using interview techniques. In this study, ethnographic approach will be simplified in a series consisting of four stages, namely 1) determining informants, 2) interviewing informants, 3) conducting ethnographic interview analysis, 4) analyzing components. Simplification of these steps is carried out as a simplification without reducing the effectiveness of ethnographic research. The data used in this study are classified into two types, namely primary data and secondary data. Primary data obtained based on the results of interviews with relevant sources. Secondary data was obtained based on texts related to the traditions of the Bunak tribe, East Nusa Tenggara and oral tradition poetry texts in the Bunak language given by research sources. Based on the results of data analysis it was found that there are three values of local wisdom in the Takneul oral tradition of the Bunak tribe, East Nusa Tenggara, namely 1) great values related to sadness or lamentation, 2) great values related to consolation or humor, and 3) great values related to love and affection.